Rural profile of oral squamous cell carcinoma (OSCC) survival patients attending in tertiary level hospital in Bogura: a hospital based retrospective observational study. - Parometa Barma; Ibrahim Khalil; Tanzima Yeasmin (Update Dental College, 2020)
Developing country like Bangladesh among 90% of oral malignant neoplasm are arising from squamous layer of oral epithelium which are third leading of this country with severe disfiguration, functiolaesa, psychological impairments and socio-economic hardship. In this study we found the prevalence of OSCC was 6.5% among total cancer patients in the two tertiary level hospitals of Bogura. Male (70%) are affected more than in females (30%). In response to male and female parameter, sex distribution ratio was 2.3:1. The prevalent average age was 55.40 years. About 80% of ulcer site was buccal mucosa then 10 % were lip mucosa. About 80% people were habituated by betel nut, leaf with tobacco chewers. Moreover 46.7% of them were maltreated by quack doctors before. Majority of the patient was in Grade II (56.7%). Correlation between variable in respect of age and cancer grading was explained. According to these study OSCC patients in north bangle region like Bogura was quite high on ( significant p-value ≤ 0.05). Description of oral squamous cell carcinoma on the basis of demographic and clinical profile was the major aim . Most of the cases report with intermediate grade of the disease which often leads to decrease the chance of survival of a patient. So new strategies should be considered to overcome the present situation must be undertaken by oral health programs for the early diagnosis and prevention, build up awareness and management and follow up of oral cancer. Update Dent. Coll. j: 2020; 10 (1): 3-5